2013
DOI: 10.3171/2013.9.focus13345
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of cavernous sinus meningiomas: evolution of a modern approach

Abstract: Cavernous sinus meningiomas (CSMs) are challenging lesions for the skull base neurosurgeon to manage given their close association with cranial nerves II–VI and the internal carotid artery. In the 1980s and early 1990s, with advancements in microsurgical techniques, increasing knowledge of the relevant microsurgical neuroanatomy, and the advent of advanced skull base surgical approaches, the treatment of CSMs involved attempts at gross-total resection (GTR). Initial fervor for a surgical cure waned, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 56 publications
1
35
1
3
Order By: Relevance
“…Even today with modern microsurgical techniques, resection of meningio- mas involving the CS is associated with high morbidity regardless of the size of the entire tumor. 1,9,11,12,19,23,24 When resection is contemplated, it is most often limited to the lateral compartment of the CS, followed by observation, or radiation therapy for symptomatic patients in order to reduce the rate of morbidity. 1,14,17,19,23,27,28 Although theoretically certain physical characteristics of the tumors, such as their hard or soft texture, the extent of their calcification, and/or the degree to which they are vascularized, would not prevent gross-total removal, they are nonetheless factors in determining whether more than 1 surgical session would be required.…”
Section: Discussionmentioning
confidence: 99%
“…Even today with modern microsurgical techniques, resection of meningio- mas involving the CS is associated with high morbidity regardless of the size of the entire tumor. 1,9,11,12,19,23,24 When resection is contemplated, it is most often limited to the lateral compartment of the CS, followed by observation, or radiation therapy for symptomatic patients in order to reduce the rate of morbidity. 1,14,17,19,23,27,28 Although theoretically certain physical characteristics of the tumors, such as their hard or soft texture, the extent of their calcification, and/or the degree to which they are vascularized, would not prevent gross-total removal, they are nonetheless factors in determining whether more than 1 surgical session would be required.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] Furthermore, in case of small asymptomatic meningiomas, considering the very slow (or even absent) growth rate of these tumours, a "wait and scan" approach appears to be a safe and more than reasonable strategy. 25 Despite the real benefit of an aggressive intracavernous surgery is actually debated, some selected circumstances may still require more aggressive approach. This is the case of there are some rare eveniences (mainly recurrences resistant to all treatment attempts) in which a very aggressive surgery of complete CS resection with carotid revascularization can be seen as a "salvage therapy".…”
Section: Surgical Managementmentioning
confidence: 99%
“…25,51 Tentatively, in order to respect this assumption we propose the following treatment algorithm.…”
Section: Conclusion: Evolution Of a Modern Treatmentmentioning
confidence: 99%
“…An MRI-based volumetric analysis of 113 incidental meningiomas showed that of tumours arising from the skull base (38/113), only 34% demonstrated growth at 4 years of follow-up 1. Our case is different in that the patient presented with symptoms; further, small radiological progression in the cavernous sinus, as opposed to the base of skull overall, may translate into significant symptoms due to the regional anatomy.…”
Section: Discussionmentioning
confidence: 63%